Anthocyanin profiles and color parameters of fourteen grapes and wines from the eastern foot of Helan Mountain in Ningxia - Huawei Chen; Miaomiao Wang; Lijian Zhang; Fuxian Ren; Yutao Li; Yong Chen; Yunqi Liu; Zhenwen Zhang; Qingqing Zeng (Food Chemistry: X)
To identify wine grape cultivars (Vitis vinifera) with superior color properties for wine production, the anthocyanin composition and color characteristics of fourteen cultivars and their wines were investigated. Grapes and wines from ‘Dornfelder’, ‘Dunkelfelder’, and ‘Malbec’ cultivars exhibited significantly higher total phenolic contents. At harvest, ‘Dornfelder’ grapes and wines exhibited the highest total anthocyanin contents, with values of 249.94 mg/kg in grapes and 1686.76 mg/L in wines, significantly higher than other cultivars. PCA and PLS-DA analyses identified malvidin-3-O-(trans-6-O-coumaryl)-glucoside as a common differential metabolite in both grapes and wines across all cultivars. Correlation analysis revealed that non-acylated anthocyanins (r = 0.68) have a more significant impact than acylated anthocyanins (r = 0.28) on color chromatic diversity in grapes and wines (P < 0.05). These findings suggest that wines produced from ‘Dornfelder’ grapes are particularly valuable for their superior color properties and high individual anthocyanin contents. This study addresses a gap in comparative anthocyanin analysis among cultivars and provides valuable insights for grape growers and winemakers seeking to optimize grape selection for improved wine quality.